Nutritional effects, toxicity and haematology studies of the ethanolic root bark extract of Hymenocardia acida Tul (Euphorbiaceae) - Paul N. Olotu, Ijeoma A. Olotu, Mighi B. Kambasha, Abubakar Ahmed, Ukpe Ajima, Temitayo L. Ohemu, Victoria A. Okwori, Dalen G. Dafam, Francis M. Agwom, Jane David, Emmanuel U. Onche (Journal of Applied Pharmaceutical Science, 2017)
The plant Hymenocardia acida has been used traditionally for decades in Northern Nigeria for the management of different types of pain such as chest-pain, rheumatic pain, tooth ache etc. It is also claimed to be beneficial in the ethno-medicinal management of sickle cell anaemia. The present study evaluates the nutritional properties, toxicity and haematological profile of the ethanolic root bark extract of the plant. Investigation of the acute toxicity of the extract in mice showed it to be safe and well tolerated on oral administration even up to doses of 6,000 mg/kg body weight. Histopathological studies on chronic administration of the extract in mice showed no observable organ damage at low dose but at higher doses, a focal area of hepatic necrosis was observed. The globule cells of the intestine were covered with progressive mucin and lymphocyte proliferations were observed within the spleen. Analysis of the blood parameters showed very significant increase in red blood cell count. The results obtained provide a rational basis for some of the uses of the plant in traditional medicine practice.
Keywords: Nutrition, Acute toxicity, chronic toxicity, Haematology, Hymenocardia acida.